Monitoring of Water Quality and Pollution Index of Situ Tirta Marta Spring, Purbalingga Using The Storet Method - Aisyah Fakhirah; Anisa Dwi Apriani; Vina Widyantari; Muhammad Kadafi; Syafiq Hariri; Gangsar Edi Laksono (Applied Environmental Sustainability and Technology, 2026)
Situ Tirta Marta Spring is a spring-based water tourism area that also supports fisheries, agriculture, and community water needs in Karangcegak Village, Purbalingga Regency. This study aimed to assess water quality and determine the pollution status of Situ Tirta Marta Spring using the STORET method. A quantitative descriptive approach was applied. Water samples were collected on 4 and 11 April 2026 using grab sampling at two purposively selected monitoring points representing the upstream spring section (S1) and the downstream area adjacent to agricultural and fishery activities (S2). The measured parameters included temperature, total dissolved solids (TDS), pH, dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), and electrical conductivity (EC). The results showed that temperature, TDS, pH, BOD, and COD met the Class II water quality standards of Government Regulation No. 22 of 2021. However, DO concentrations at S1 (1.40 mg/L) and S2 (2.95 mg/L) were below the minimum standard of 4 mg/L, indicating reduced oxygen availability in the aquatic system. Comparison with Minister of Health Regulation No. 32 of 2017 also indicated that temperature, TDS, and pH were within relevant standards for public bathing and sanitation-related uses, whereas DO did not comply. The STORET score was -4, indicating that the spring water is lightly polluted. These findings indicate mild environmental pressure and highlight the need for improved sanitation, visitor activity control, waste management, and regular water quality monitoring.